STUDY HERB ANATOMIC STRUCTURE OF THYMUS DIMORPHUS KLOK. ET SHOST - V. V. Bubenchikova; Yu. A. Starchak (Фармация и фармакология (Пятигорск), 2015)
The article shows the results of an atomic structure of a herb of Thymus dimorphus. Mi-crodiagnostic signs were explored and determined during the study. Stem has a roundish-tetrahedral shape and a non-fascicular formation. Stomata are of the diacytic type. An availability and texture of the simple and glandular hairs are determined. So all along the Thymus dimorphus stem we have found bi- or threecellular thick-walled hairs with warty cuticle, more often they are cranked, the hairs of 5-9 cells with slightly warty surface, with grand content and glandular hairs on the bi- or threecellular stem with an elongated head and widened basal cell.There are simple unicellular hairs with slightly pointed apex and warty cuticle along the epidermis of a leaf, as well as bi- or threecellular cranked thick-walled hairs with fine-pointed apex with warty surface, the simple hairs of 4-8 cells with slightly widened cell walls and slightly warty cuticle.During the research of the flower's parts (calyx and corolla) a kind of pubescence by the different types of hairs and a shape of epidermal cells were determined. There are essential oil glands in the epidermis of the stem, leaf, calyx and corolla.The derived research results will allow identification of a specific belonging of thymes basing on diagnostic sings